Investigation of a transonic separating/reattaching shear layer by means of PIV. Issue 1 (January 2015) - Scharnowski, S.; Kähler, C.J.
Abstract: The separating/reattaching flow over an axisymmetric backward-facing step is analyzed experimentally by means of particle image velocimetry (PIV). The main purpose of the measurements is the investigation of the mean flow field as well as of the Reynolds stress distributions at a Mach number of 0.7 and at a Reynolds number of 3.3×10 5 based on the step height. Due to the strong progress of optical flow measurements in the last years it was possible to resolve all flow scales down to 180 μ m ( ≈ 1 % of the step height) with high precision. Thanks to the high spatial resolution it was found for the first time that the Reynolds stress distribution features a local minimum between the first part of the shear layer and a region inside the recirculation region. This implies a more complex wake dynamics than assumed before.